Surface Water Quality in Gorakhpur City, Uttar Pradesh - Kumar, Varun; Goswami, K. P. (National Geographical Journal of India, 2022)
Water is an essential component for the survival of life on the Earth. It contains minerals, which is important for human beings as well as plant and aquatic life. The availability of water both in terms of quality and quantity is essential for the very existence of mankind. There is heavy extraction of water for domestic, industrial and agricultural purposes. Lack of awareness and civic sense, use of inefficient methods and technology; lead to more than 50% of water wastage in the domestic, agricultural & industrial sectors. Water pollution is rendering much of the available water unsafe for consumption. In India, most of the population is dependent on surface water as the source of drinking water supply. Water quality index (WQI) provides a single number that expresses overall water quality at a certain location and time, based on several water quality parameters. Calculation of water quality index using standard method given by the Horton, Bureau of Indian Standards (BIS, 2003) and the Indian Council of Medical Research (ICMR, 1975). The present work is based on both primary and secondary data and aims to assess the water quality index (WQI) of the surface water of river Rapti and various ponds situated in Gorakhpur City. The analyzed data are compared with standard values recommended by BIS and ICMR. Ten parameters are considered for calculating the WQI such as: pH, Total Hardness, Total Alkalinity, Total Dissolved Solid (TDS), Calcium, Magnesium, Chloride, Sulphate, Nitrate, and Dissolved Oxygen (DO) and also calculate the seasonal variations of Physico-chemical parameters on the water quality of Gorakhpur city. The spatial distribution maps of the water quality index are prepared by using Arc GIS software. Data tabulation, Arithmetical calculation and diagrams are prepared in MS Excel.